The Pulmonary Embolism Response Team: Why and How? - Channick, Richard N. (Seminars in Respiratory and Critical Care Medicine, 2021)
Treatment of patients with intermediate and high-risk pulmonary embolism (PE) is a controversial area. Many therapeutic options exist, and deciding on appropriate treatment can be difficult. In addition, multiple specialties are often involved in the care of PE patients. To better organize the response to serious PE patients, several hospitals and academic centers throughout the world have created pulmonary embolism response teams (PERTs). The goal of a PERT is to have a single multidisciplinary team of experts in thromboembolic disease, who can respond rapidly to patients with acute PE, and offer consultation and implementation of the full spectrum of therapeutic options. PERT teams were modeled after rapid response teams and are meant to generate a prompt, patient-specific plan for patients with PE without having to consult multiple individual specialists. Data are emerging demonstrating the value of PERTs in reducing hospital length of stay and, possibly, patient outcomes.
Keywords: pulmonary embolism; multidisciplinary team; pulmonary embolism response teams; venous thromboembolism